Rashid Ahmed Siddiqui's Autobiography "Ashifat Bayani Meri" in a Social Context - Rahman, Muhammad; Noreen, Uzma; Saddique, (Makhz (Research Journal), 2025)
"Ashfat Bayani Meri" is the autobiography of Rashid Ahmed Siddiqui. He was born in 1894 in a village of Jaunpur district of UP. He lived in Jaunpur till his matriculation. Then he came to Aligarh for higher education. When a college was established in 1912, he was reinstated as a professor. When the university was established, a department of Urdu literature was also established in it and he was made the head of the department. He died in 1977. He was also awarded the Sahitya Academi Award and the Padma Shri for literature and education. His famous works include "Khandan", "Ganj Hai Granmayah" and "Taniyat Wamzahakat". Rashid Ahmed Siddiqui's autobiography "Ashfat Bayani Meri" is actually a commentary on your Aligarh University (MAO College). In it, you have also described different aspects of your life. However, the love for Aligarh and its long mention do not let the rest of your life shine in the eyes of the reader and it feels as if this autobiography is dedicated to Aligarh alone. A special thing about this autobiography is that Rashid Ahmed Siddiqui has also mentioned various personalities in it. While reading this autobiography, the reader goes into the valley of history, the beauty of words and sentences, the decency of language, the skill of using poetry, and many good things at the same time. This also indicates the dark corners of Rashid Sahib's academic life. And there are "funnies".